A practical guide to undergraduate radiology education. Issue 12 (December 2022) - Robinson, E.; Little, D.
Abstract : The new Royal College of Radiologists (RCR) undergraduate curriculum and the impending introduction of a universal General Medical Council (GMC) medical licensing assessment (MLA) for all undergraduates in the UK heralds a new era of undergraduate radiology education. This is a practical guide to both implementing and delivering undergraduate radiology education using our experience and the available literature. It aims to provide ideas so that more universities and radiologists can integrate radiology into everyday learning and are ready to embrace the new RCR curriculum and GMC MLA. Allied to this, strategies are provided to show how to encourage early undergraduate interest in a career in radiology. Highlights: The GMC MLA content map specifically includes clinical imaging. Consider using normal cases & technology to improve interactivity for undergraduates. Consider offering student choice or elective placements in radiology.